Factors Associated with the Year of Admission and The IQ of Engineering Students at A Public University in Peru - López, Pedro Pablo Rosales; Pacheco, Mercedes Puca; Puca, César Augusto Tacuri; Moreno, Mariela Elizabeth Andagua; Broncano, Christian Albert Aguirre; Ricardo, Ramirez Fernandez Ender; Esteban, Bernard Edwin Yapo (Journal of Ecohumanism, 2025)
This study investigates the evolution of intelligence quotient (IQ) among students in the Faculty of Industrial Engineering at the Universidad Nacional Mayor de San Marcos. The aim is to determine the influence of three factors on IQ: age, year of study, and month of university enrollment. Data was collected from a group of students using the Wechsler Adult Intelligence Scale (WAIS-IV), a standardized instrument for assessing general intelligence in individuals aged 16 to 90. An orthogonal experimental design was employed to compare mean IQ scores across different groups defined by age, year of study, and their combinations, using a three-way analysis of variance and interaction plots. Results confirm the influence of both age and year of study on IQ, as well as the existence of an interaction effect between both variables. These findings suggest that both natural cognitive development and exposure to academic training contribute to changes in IQ throughout the university trajectory. Additionally, an opportunity is identified for future research to delve deeper into the underlying mechanisms of these changes and explore strategies to optimize students’ intellectual development.